Assessment of Spatial Variation of Surface Water Quality at Gebeng Industrial Estate, Pahang, Malaysia - Islam, Mir Sujaul; Hossain, Mohamed Amjed; Nasly, Mohamed Ali; Edriyana, Abd Aziz (Penerbit UMP, 2012)
Gebeng Industrial Estate is the main industrial town of Pahang, where, Tunggak is a strategic river. The anthropogenic impact on the river is as a result of rapid industrialization in Gebeng. The river is of particular importance in the study of surface water quality status because effluents from industries of Gebeng discharge into it thereby deteriorating the quality. Water quality parameters were analyzed across the river with the objective to disclose the spatial variation of the river water quality. To fulfill the objective, water samples were collected monthly from 10 sampling stations and physico-chemical parameters were analyzed using APHA & HACH standard methods. Heavy metals were determined using ICP-MS. Data analyses were done using SPSS 16.0 statistical software. The study reveled that, pollution from non-point source was associated with runoff from construction sites of newly developed industrial areas and the point source contributing the major pollutants especially from industrial wastes. According to the Interim INWQS, Malaysia based on DO, COD, ammoniacal nitrogen and some selected trace elements, major part of the river specially the mid-region was categorized as class V (very highly polluted) while some part was found in class IV (highly polluted) and rest in class III (polluted) as well. Furthermore, classification of the river based on DOE-WQI showed that seven (7) stations (2-8) were in class IV (highly polluted), station 1, 9 & 10 were found to be polluted. It is concluded that pollution is higher in the middle stations of the river compared to the upper and lower stream.